5‐Hydroxymethylcytosine profiling from genomic and cell‐free DNA for colorectal cancers patients. Issue 5 (26th March 2019) - Gao, Pingting; Lin, Shengli; Cai, Mingyan; Zhu, Yan; Song, Yanqun; Sui, Yi; Lin, Jing; Liu, Jiaxiuyu; Lu, Xingyu; Zhong, Yunshi; Cui, Yuehong; Zhou, Pinghong
Abstract: 5‐Hydroxymethylcytosine (5hmC) is a DNA modification that is generated by the oxidation of 5‐methylcytosine (5mC) in a reaction catalyzed by the ten‐eleven translocation (TET) family enzymes. It tends to mark gene activation and affects a spectrum of developmental and disease‐related biological processes. In this manuscript, we present a 5hmC selective chemical labelling technology (hmC‐Seal) to capture and sequence 5hmC‐containing DNA fragments with low input. We tested 10 tumour/adjacent colon cancer tissues and 10 tumour/healthy plasma samples. Furthermore, we tested if this methodology could generate the 5hmC differential genes among cancer patients, healthy controls and precancerous adenoma patients from plasma. Robust cancer‐specific epigenetic signatures were identified for colon cancers. The results show that 5hmC is mainly distributed in gene active regions. The results also indicate the potential application of 5hmC change signals in early stage of colon cancer, even show potential in the diagnosis of precancerous adenoma. We demonstrated the robustness of the 5hmC‐Seal method in tissue and cell‐free DNA (cfDNA) as potential biomarkers. Moreover, this study provides the potential value and feasibility of 5hmC‐Seal approach on colorectal cancer (CRC) early detection. We believe this strategy could be an effective liquid biopsy‐based diagnosis and a potential prognosis method for colon cancer using cfDNA.